Cluster-based development: A Chinese cluster policy - Jankowiak, Anna H. (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
Clusters and links between companies are becoming increasingly important in the dynamically changing global economy. Chinese clusters have been developing for many years, although they are not at a level of development such as the Japanese or American ones. Many of them are powerful entities responsible for a significant percentage of world production and trade. The Chinese authorities support the specialization of regions in specific production, which began with the open door policy and the transfer of the Japanese model “one village, one product” to the Chinese economy. The paper presents a theoretical conceptualization of the cluster idea, taking into account various approaches to this problem and outlines the development policy based on clusters in China. The main aim of this article is to present cluster-based development approach as a part of cluster policy and development in China
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 486, s. 71-79
Keywords: clusters; industrial clusters; China; cluster-based development; klastry; klastry przemysłowe; Chiny; polityka rozwoju oparta na klastrach